Selective and Gram-Scale Synthesis of [6]Cycloparaphenylene - Kayahara, Eiichi; Patel, Vijay Kumar; Xia, Jianlong; Jasti, Ramesh; Yamago, Shigeru (Synlett, 2015)
A selective, practical, and large-scale synthesis of [6]cycloparaphenylene, the second smallest cycloparaphenylene to be synthesized, was achieved in nine steps starting from commercially available 1,4-dibromobenzene and 4′-bromobiphenyl-4-ol. The key intermediate, cis-1,4-(4-bromophenyl)-1,4-bis(triethylsiloxy)cyclohexa-2,5-diene, was prepared on a large scale (>20 g) and was selectively dimerized to form a cyclic precursor of [6]cycloparaphenylene by platinum-mediated assembly and subsequent reductive elimination. Deprotection of the triethylsilyl group and subsequent tetrachlorostannic acid (H2SnCl4)-mediated reductive aromatization gave [6]cycloparaphenylene in 23% overall yield from the commercially available substrates on gram scale.
Keywords: cyclophanes; cyclizations; organometallic reagents; platinum; tin